Dickinson unbound paper, process, poetics - Socarides, Alexandra (New York ; Oxford : Oxford University Press, 2012)
Alexandra Socarides takes readers on a journey through the actual steps and stages of Emily Dickinson's creative process. In chapters that balance attention to manuscripts, readings of poems, and a consideration of literary and material culture Socarides takes up each of the five stages of Dickinson's writing career.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: Dickinson, Emily, -- 1830-1886 -- Criticism and interpretation